Pericellular interphotoreceptor matrix dictates outer retina critical surface tension. (February 2018) - Gonzalez-Fernandez, Federico; Fornalik, Mark; Garlipp, Mary Alice; Gonzalez-Fernandez, Priscilla; Sung, Dongjin; Meyer, Anne; Baier, Robert
Abstract: Retinal detachments create two pathological surfaces, the surface of the outer neural retinal, and an apical retinal-pigmented epithelium (RPE) surface. The physicochemical properties of these two new surfaces are poorly understood. At a molecular level little is known how detachments form, how to optimize reattachment, or prevent extension of the detachment. A major limitation is lack of information about the biophysical consequences of the retina–RPE separation. The primary challenge is determining the molecular properties of the pathological interface surfaces. Here, using detached bovine retina, we show that this hurdle can be overcome through a combination of biophysical and ultrastructural approaches. The outer surface of freshly detached bovine neural retina, and isolated molecular components of the outer retina were subjected to: 1) Contact angle goniometry to determine the critical surface tension of the outer retinal surface, isolated insoluble interphotoreceptor matrix (IPM) and purified interphotoreceptor retinoid binding protein (IRBP); 2) Multiple attenuated internal reflectance infrared (MAIR-IR) spectroscopy was used to characterize the molecular composition of the retinal surface. MAIR-IR depth penetration was established through ellipsometric measurement of barium-stearate films. Light microscopy, immunohistochemistry and electron microscopy defined the structures probed spectroscopically. Furthermore, the data were correlated to IR spectra of docosahexaenoic acid, hyaluronan, chondroitin-6-sulfate and IRBP, and imaging by IR-microscopy. We found that the retinal critical surface tension is 24 mN/m, similar to isolated insoluble IPM and lower than IRBP. Barium-stearate calibration studies established that the MAIR-IR spectroscopy penetration depth was 0.2 μm. Ultrastructural observations and MAIR-IR studies of isolated outer retina components determined that the pericellular IPM coating the outer retinal surface is primarily responsible for these surface properties. The critical surface tension of detached bovine retina is dictated not by the outer segments, but by a pericellular IPM covering the outer segment tips. Highlights: Physiochemical and structural properties of the detached bovine outer retinal surface were accessed. A 0.28 μm thick matrix of critical surface tension 24 mN/m, typical of low adhesive "Theta Surfaces", coats the retina. Multiple attenuated internal reflectance infrared (MAIR-IR) spectroscopy probes the surface to a depth of 0.2 μm. The pericellular matrix contains chondroitin-6 sulfate, interphotoreceptor retinoid-binding protein, but not DHA. The critical surface tension of detached retina is dictated by a pericellular matrix covering the outer segment tips.